Effect of Super Absorbent Polymer and Soil Texture Affecting the Physiological Response of Maize (Zea mays L.) under Water Deficit Stress - Alireza Moeini; Ali Neshat; Najme Yazdanpanah; Amin Pasandi Pour (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In order to evaluate the role of super absorbent polymer (SAP) for mitigating the water deficit stress at sandy and clay-loam soils, the effect of five values of SAP (0, 0.1, 0.2, 0.4 and 0.8 g.kg-1 soil), three water treatment (the relative soil water content of 80, 60, and 40%) and two soil textures (sandy and clay-loam) on biomass production, photosynthetic pigments, leaf gas exchange parameters, leaf relative water content (RWC), electrolyte leakage (REC), proline content, catalase, super oxide dismutase, and ascorbate peroxidase activity. The experiment was carried out with a factorial arrangement based on complete randomized design in triplicates at the Agricultural and Natural Resources Research and Education Center, Kerman, Iran. The results revealed that water deficit stress caused a significant decrease in net photosynthesis rate, leaf stomatal conductance, chlorophyll a+b content, RWC, plant height, and dry matter production of maize. CAT, SOD, APX activity, REC, and proline were elevated with increasing water deficit stress levels. Application of SAP under water deficit stress increased the net photosynthesis (32.3%), stomatal conductance (38%), chlorophyll a+b (23.9%), RWC (11.9%), and dry matter production (24%), while it decreased REC (10.8%), proline content (66.9%), CAT (42.7%), SOD (33.2%), and APX activity (34.3%) as compared to control. It can be concluded that application of SAP (0.8 g.kg-1 soil) improved plant growth of maize under water deficit stress through increasing the water holding capacity in soil.